Design of Irrigation Channel Network Connectivity and Tertiary Channels in Menten Village, Rambutan District South Sumatra to Optimize Agricultural Land - Sakura Yulia Iryani; Agus Lestari Yuono; Regina BR Manalu; Reini Silvia Ilmiaty (UKaRsT, 2023)
South Sumatra Province is a province that is flowed by many rivers, including the Musi River, the longest river on the island of Sumatra. The condition of inadequate irrigation infrastructure means that farmers in Menten Village can only plant one crop per year. This study aimed to determine the irrigation water needs of tertiary canals and design the dimensions of connectivity and tertiary channels.  Repairing the irrigation network in the village is planned to increase the productivity of agricultural land to two plantings in one year with a cropping pattern of rice and crops. This research was conducted following the following stages Calculation of Irrigation Water Needs, Calculation of Surface Runoff Discharge, Calculation of Channels Design Discharge, Calculation and determination of the dimensions of Connectivity and Tertiary Irrigation Channels. The study results obtained a Need Field Requirement (NFR) value of 1.572 l/s/ha with a maximum irrigation water requirement of 2.418 l/s.ha. To increase menten agricultural yields, a planting pattern of 2 times is planned. The planned channel is an open trapezoidal channel that functions as a carrier channel and a discharge channel namely rice and crops. There are three connectivity irrigation channels. While there are 25 tertiary irrigation canals. The results of this research can be used reference to improve irrigation systems that are still not optimal.